1991
DOI: 10.1111/j.1549-0831.1991.tb00438.x
|View full text |Cite
|
Sign up to set email alerts
|

Returns vs. Endowments in the Earnings Attainment Process for Metropolitan and Nonmetropolitan Men and Women1

Abstract: Three explanations typically are offered for differences in earnings: (1) individuals have different levels of human capital and hold different jobs (endowments differ), (2) rewards to human capital and job characteristics differ (returns differ), and (3) some combination of differences in endowments and returns explain variations in earnings. We argue that the structure of labor markets in nonmetropolitan (nonmetro) areas differs from that in metropolitan (metro) areas such that returns, as well as endowments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(27 citation statements)
references
References 36 publications
1
26
0
Order By: Relevance
“…Poverty rates among single female-headed families are also shown to be higher where a greater proportion of the population is under 15 years of age and for nonmetro areas. The first finding points to the linkages between the "feminization" and "juvenilization" of poverty (Bianchi 1999), while the latter is suggestive of the fact that rural women receive lower labor market returns (i.e., earnings) for their human capital and occupation compared to their urban counterparts (McLaughlin and Perman 1991) and face more restricted employment opportunities. Last, we tested two-way interactions between the Borderland dummy variable and each of the other independent variables, but found no significant interaction effects associated with poverty among single female-headed families.…”
Section: Multivariate Models Of Poverty Levels By Family Typementioning
confidence: 95%
“…Poverty rates among single female-headed families are also shown to be higher where a greater proportion of the population is under 15 years of age and for nonmetro areas. The first finding points to the linkages between the "feminization" and "juvenilization" of poverty (Bianchi 1999), while the latter is suggestive of the fact that rural women receive lower labor market returns (i.e., earnings) for their human capital and occupation compared to their urban counterparts (McLaughlin and Perman 1991) and face more restricted employment opportunities. Last, we tested two-way interactions between the Borderland dummy variable and each of the other independent variables, but found no significant interaction effects associated with poverty among single female-headed families.…”
Section: Multivariate Models Of Poverty Levels By Family Typementioning
confidence: 95%
“…Previous studies showed that rural women have fewer stable employment opportunities and earn less than urban women (Lichter 1989;McLaughlin and Perman 1991;Wells 2002). Our study highlights yet another aspect of inequality among these two groups of women-inequality in access to family-friendly benefits.…”
Section: Discussionmentioning
confidence: 52%
“…Lichter (1989) found that rural women were more likely to experience underemployment than urban women. Even after controlling for education, urban women earn more than rural women (McLaughlin and Perman 1991;Smith and Glauber 2013). Despite this rich tradition of research on rural-urban inequality among women, we know very little about ruralurban inequality in family-friendly benefits.…”
Section: Rural-urban Economic Disparitiesmentioning
confidence: 92%
See 2 more Smart Citations